Neuropatia periférica diabética - caracterização dos sinais e sintomas nos membros superiores e implicações para a fisioterapia - Balbino, Milena Stephanie Bezerra (Universidade Federal de São Carlos, 2024)
Diabetes mellitus (DM) is an important public health problem due to its high incidence and the condition of persistent hyperglycemic, which is directly associated with several comorbidities. Among DM comorbidities we can highlight the diabetic peripheral neuropathy (DPN), which manifests significantly in the lower limbs and is a risk factor for the development of ulcerations on the feet of those with DM. Although some studies have also suggested a manifestation of DPN in the upper limbs, data regarding the occurrence of DPN in this segment and its relation with the manifestation in the lower limbs are scarce. Objectives: This study aims to characterize and compare the manifestation of DPN in the upper limbs (dominant and non- dominant) between people with DM who have and have not manifested DPN in the lower limbs. Methods: Forty-four individuals with DM (diagnosis time: 10.4 ± 6.7 years) participated in this study. The participants were divided into two groups, each made up of 8 women and 14 men. One group was composed of individuals with DM and no diagnosis of DPN (n =22, age = 49 [41 – 55] years), while the other was composed of individuals with DM and DPN (n = 22, age = 51 [43 – 57] years). The evaluation of DPN manifestation in the upper limbs was performed by a questionnaire on symptomatology and clinical tests of hand tactile and vibratory sensitivity, handgrip strength test, and the Jebsen-Taylor Test. The groups were compared using Student’s t or Mann-Whitney according to the distribution of the data. The chi-square test (χ2) and Fisher's exact test were used for categorical data. Spearman's correlation test (r) was also used to analyze the association between lower limb DPN and upper limb DPN symptoms. For all analyses, the significance level was set at 5%. Results: The group with DM and DPN presented higher levels of fasting glycemia and glycated hemoglobin (p < 0.05), as well as lower tactile sensitivity in the course of the median and ulnar nerves of the dominant hand and the ulnar nerve of the non-dominant hand (p < 0.05), lower vibration sensitivity of the non- dominant hand (p = < 0.05), and longer time to perform the Jebsen-Taylor test with the dominant and non-dominant hand (p < 0.05). Correlations were observed between the severity of DPN in the lower limbs and the subsequent variables related to DPN in the upper limbs: DPN symptoms, tactile and vibratory sensitivity, and manual function. Conclusion: Lack of glycemic control appears to be associated with the development of DPN. The presence and severity of DPN appears to be associated with a reduction in tactile and vibratory sensitivity of the hands, and with functional deficits in the hands of individuals with DM.
Diabetic peripheral neuropathy - characterization of signs and symptoms in the upper limbs and implications for physiotherapy
Keywords: Comorbidades; Diabetes; Extremidade superior; Reabilitação; OUTROS